Generation of a Novel Bacteriophage Library Displaying scFv Antibody Fragments from the Natural Buffalo Host to Identify Antigens from Adult Schistosoma japonicum for Diagnostic Development. - Christopher G Hosking; Hamish E G McWilliam; Patrick Driguez; David Piedrafita; Yuesheng Li; Donald P McManus; Leodevico L Ilag; Els N T Meeusen; Michael J de Veer (Public Library of Science (PLoS), 2015)
The development of effective diagnostic tools will be essential in the continuing fight to reduce schistosome infection; however, the diagnostic tests available to date are generally laborious and difficult to implement in current parasite control strategies. We generated a series of single-chain antibody Fv domain (scFv) phage display libraries from the portal lymph node of field exposed water buffaloes, Bubalus bubalis, 11-12 days post challenge with Schistosoma japonicum cercariae. The selected scFv-phages showed clear enrichment towards adult schistosomes and excretory-secretory (ES) proteins by immunofluorescence, ELISA and western blot analysis. The enriched libraries were used to probe a schistosome specific protein microarray resulting in the recognition of a number of proteins, five of which were specific to schistosomes, with RNA expression predominantly in the adult life-stage based on interrogation of schistosome expressed sequence tags (EST). As the libraries were enriched by panning against ES products, these antigens may be excreted or secreted into the host vasculature and hence may make good targets for a diagnostic assay. Further selection of the scFv library against infected mouse sera identified five soluble scFv clones that could selectively recognise soluble whole adult preparations (SWAP) relative to an irrelevant protein control (ovalbumin). Furthermore, two of the identified scFv clones also selectively recognised SWAP proteins when spiked into naïve mouse sera. These host B-cell derived scFvs that specifically bind to schistosome protein preparations will be valuable reagents for further development of a cost effective point-of-care diagnostic test.